2006
DOI: 10.1021/cm061534n
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structural Modeling and Gas Adsorption Analysis of Cagelike SBA-16 Silica Mesophases Prepared in a F127/Butanol/H2O System

Abstract: A detailed characterization of large-pore cagelike mesoporous SBA-16 silica materials with tailored pore dimensions is reported. The materials were synthesized in a EO106PO70EO106 (F127)−butanol−H2O system under mildly acidic conditions, and the pore diameters were tailored by varying the hydrothermal treatment temperature. Structural information was acquired by full-profile analysis of powder X-ray diffraction (XRD) patterns. High-resolution diffraction data were obtained for all the materials using synchrotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 46 publications
(93 reference statements)
6
88
0
Order By: Relevance
“…As a result, a pore sizes analysis in the entire range of micro and mesopores can be performed by the NLDFT model [11]. The pore sizes obtained by this model agree with the results derived from experimental techniques based on X-ray diffraction (XRD) or transmission electronic microscopy (TEM) for OMM type MCM-41 [48,49], SBA-15 [50] and SBA-16 [51,52].…”
Section: Bjh-kjs Imp (Adsorption Branch)supporting
confidence: 72%
See 1 more Smart Citation
“…As a result, a pore sizes analysis in the entire range of micro and mesopores can be performed by the NLDFT model [11]. The pore sizes obtained by this model agree with the results derived from experimental techniques based on X-ray diffraction (XRD) or transmission electronic microscopy (TEM) for OMM type MCM-41 [48,49], SBA-15 [50] and SBA-16 [51,52].…”
Section: Bjh-kjs Imp (Adsorption Branch)supporting
confidence: 72%
“…The shape of this hysteresis is related to the percolation phenomenon occurring throughout the desorption process at a P/P 0 of approximately 0.42 [53]. For all the samples, the capillary condensation on the primary mesopores takes places in one step, suggesting a defined pore size and a material with a high degree of arrangement [52].…”
Section: Resultsmentioning
confidence: 85%
“…An improvement for pore size analysis can be obtained by calibrating the Kelvin equation using a series of MCM-silicas of known pore diameter (obtained from XRD interplanar spacing and the mesopore volume). In this manner, a relation between capillary condensation pressures and pore size can be established and used to obtain an empirically corrected Kelvin equation valid over the calibrated range (∼ 2 -10 nm) [118,119].…”
Section: Pore Size Analysismentioning
confidence: 99%
“…The isotherm obtained may be interpreted as a type IV isotherm with an extremely broad capillary condensation step and an H3-type hysteresis loop (IUPAC classification; Kaneko 1994). The pore size distribution (PSD) calculated by NLDFT method (adsorption branch model for spherical mesopores) is broad, indicating a range from 0.5 to 30 nm with two maxima centered at ~5.3 nm (corresponding to the pore entrance size) and ~9.1 nm, respectively (Kleitz et al 2006), with the latter likely representative of the main spherical mesopores. This result is in contrast with that obtained for mesostructured stishovite quenched at 14 GPa (Stagno et al 2014) after plasma treatment that showed a type II isotherm with no hysteresis.…”
Section: Resultsmentioning
confidence: 99%